4:50 from Paddington : a Miss Marple mystery - Christie, Agatha, 1890-1976 (Christie, Agatha, 1890-1976. Miss Marple mystery., 2022)
"For an instant the two trains ran side by side. In that frozen moment, Elspeth McGillicuddy stared helplessly out of her carriage window as a man tightened his grip around a woman's throat. She watched on as the body crumpled. Then the other train drew away. But who, apart from Mrs. McGillicuddy's friend Jane Marple, would take her story seriously? After all, there are no other witnesses, no suspects, and no case. How could there be, with no corpse and no one missing? Miss Marple asks her highly efficient and intelligent young friend Lucy Eyelesbarrow to infiltrate the Crackenthorpe family, who seem to be at the heart of this mystery, and help unmask a murderer."--